AI-Driven Teaching Capacity Building for English Teachers: A Professional Development Program for MGMP Tanjung Jabung Timur - Fortunasari; Mukminin, Amirul; Hidayat, Marzul; Gowon, M; Masita, Ella; Iqroni, David; Heryanti, Reny (Jurnal Karya Abdi Masyarakat, 2026)
This community service program aimed to strengthen the technopedagogical competence of junior high school English teachers in Tanjung Jabung Timur Regency through the integration of Artificial Intelligence (AI) into classroom practice. The program adopted a participatory, needs-based approach involving 30 teachers from 12 schools and was implemented over seven weeks through workshops, mentoring, and classroom application. The training introduced AI concepts, ethical considerations, and hands-on use of selected applications, followed by guided implementation supported by reflective practice and continuous feedback. The results indicate notable improvements in teachers’ confidence and ability to design AI-integrated lessons, accompanied by increased student engagement and more interactive classroom dynamics. The program also contributed to a shift in teachers’ perceptions of AI from a perceived challenge to a supportive instructional partner and fostered the development of a professional learning community within the MGMP network. The novelty of this initiative lies in its mentoring-driven and practice-oriented approach tailored to rural educational contexts. The findings suggest that sustainable AI integration requires not only technical training but also ongoing professional support, collaborative structures, and alignment with local conditions.